Urban planning in areas of environmental and flood risks: The Lagoas do Norte program, in Teresina, Piauí - Lopes, Wilza Gomes Reis; Soares, Érica Cecília de Sousa; Matos, Karenina Cardoso (Seven Editora, 2024)
The population growth and the degree of urbanization of Teresina, the capital of the state of Piauí, influenced the disorderly occupation of areas closer to rivers and lagoons, which increased flood events, in addition to constituting areas of precarious infrastructure. This article discusses the relationship between the urban planning of Teresina and the conception of the Lagoas do Norte Program (PLN), highlighting its actions related to the guidelines provided for in the master plans of the municipality and the possible administrative transformations of the Municipality of Teresina. A bibliographic research was carried out on urban planning in Brazil, focusing on Sustainability, Strategic Planning and City Statute, and how such themes influenced the Master Plan of Teresina and the PLN. It was found that the PLN influenced the other subsequent plans and the possible administrative transformations of the Municipality of Teresina, focused on urban planning and the environment. It was also possible to see that the PLN presented conflicts of interest and disagreement between the actors involved, which occurred throughout the process of its implementation, verified through the local press, official documents, speeches by the technical team of the city hall and conversations with residents. It is emphasized, then, the need and importance of urban planning aimed at improving urban, social and environmental living conditions in cities. DOI:https://doi.org/10.56238/sevened2024.026-052